Navigating taxpayers attitude: Exploring support for urban sanitation surcharge in Kumasi - Oduro, Charles Yaw (Sage, 2024)
Background: Urban sanitation challenges persist in Ghana, prompting Metropolitan, Municipal, and District Assemblies (MMDAs) to explore innovative funding mechanisms such as surcharges to fund sanitation services. This study assesses property owners’ attitudes toward the imposition of sanitation surcharge for pro-poor sanitation improvement in the Kumasi Metropolis. Method: An analytical cross-sectional study was conducted among 424 property owners in the Kumasi metropolis. Structured questionnaires were utilized to solicit information from respondents using multi-stage sampling techniques. Results: Findings indicated that 36.1% of respondents were willing to pay the sanitation surcharge, while 63.9% opposed its implementation in the Metropolis. Property ownership and support for a sanitation surcharge were associated with higher odds of willingness to pay. Participants paying property rates had decreased odds of supporting the sanitation surcharge. Factors associated with pro-poor spending support included age (61-80 years) [AOR = 1.81, 95%CI = 1.60-3.82] and willingness to pay sanitation surcharge [AOR = 11.07, 95%CI = 6.63-18.49]. Protective factors against supporting pro-poor spending included residing in medium-class communities [AOR = 0.25, 95%CI = 0.08-0.81], perceiving improvement in sanitation status [AOR = 0.41, 95%CI = 0.21-0.81) and having a home toilet facility (OR = 0.65, 95%CI = 0.36-0.95). Conclusion: The study revealed a nuanced landscape where concerns about fund utilization, perceived tax burdens, and trust in local institutions significantly shape public sentiment. To enhance public acceptance and participation, policymakers should prioritize transparent communication to build trust and convey the effective utilization of funds from the sanitation surcharge.